STRATEGI PENGEMBANGAN MATEMATIKA BAGI ANAK USIA DINI - Iva Sarifah (Perspektif Ilmu Pendidikan, 2006)
This article discussed how mathematics instruction should be developed for early childhood education. Some instruction strategies are elaborated such as Developmentally Apropriate Practice, integrated learning, cooperative learning, student active learning, contextual learning, inquiry based learning, and co-parenting. In the implementation of the instructional strategies in this article puts forward a number of considerations.